Le Golphe de Saint Laurent et L'Ilse de Terre-Neuve - Bellin, Jacques Nicolas, 1703-1772 ([Paris], 1764)
Hand coloured. Prime meridian Paris. North arrow with rhumb lines. Decorative title cartouche. Relief shown pictorially. Depths shown by soundings. Bar scale in French common leagues. Includes references to detailed maps of specific regions. Includes note indicating that the interior of Newfoundland is little-known and filled with mountains, woods and lakes.